FUNGSI PERUSAHAAN PENERBANGAN , KUALITAS JASA DAN KAITANNYA DENGAN KEPUASAN KONSUMEN - Atikah Atikah; Osrita Hapsara (Universitas Batanghari Jambi, 2009)
Every company that oriented business inclusive of in it the Airline, ever expect the advantage from its effort activity. To reach the target hence each ,every company have to be powered all potency owned. Because existing emulation will make the consumer more choice by various service in execute its purchasing at the price of which vary marketing. Such in a condition, company cannot only give all mind to at product which on the market. But on the contrary also think how to to be gone through service to which on the their market can draw attention the consumer from assorted of product which on the market by other competitor, very important The Ailrline role remember the Indonesia represent the world power which geographically consisted of various thousand island which gone the round of from Sabang until Marauke. In repair of service quality so that can gratify the airline consumer require to pay attention to some attribute ( factor ) : accuracy of Time of service, and sociability in giving ,Reply to Go together the acceptance of order and handling of sigh consumer, get the Variasi Model The Personal, Freshment in obtaining service. and other service Supporter Attribute like environment , hygiene, space await the, music facility, AC ,etc. Keyword : Air line , service quality, satisfaction